2012
DOI: 10.1002/adma.201204010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Thermoelectric Performance of Ball‐Milled Bismuth Due to Spark‐Plasma‐Sintering‐Induced Interface Modifications

Abstract: Interface modification in transport properties of single elemental polycrystalline Bi via spark plasma sintering results in 'double-decoupling' (simultaneous decoupling of thermopower, electrical, and thermal conductivity) of otherwise coupled entities. In spark plasma sintering, the DC pulse current helps in controlling the nature and extent of surfaces of ball-milled Bi and hence results in six-fold improvement in the dimensionless figure of merit (ZT) relative to as-purchased samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Owing to the grain boundary scattering, the thermal conductivity of nanograined BiSbTe is lower than that of its bulk counterpart. [49][50][51][52] Impurity scattering, l i . Also, the interfacial states formed in the nanograined region can be used to increase the power factor, as proposed by Kirievsky et al 46 An example study of the coated-grain boundary is shown in Fig.…”
Section: Engineering Phonon Thermal Conductivitymentioning
confidence: 99%
“…Owing to the grain boundary scattering, the thermal conductivity of nanograined BiSbTe is lower than that of its bulk counterpart. [49][50][51][52] Impurity scattering, l i . Also, the interfacial states formed in the nanograined region can be used to increase the power factor, as proposed by Kirievsky et al 46 An example study of the coated-grain boundary is shown in Fig.…”
Section: Engineering Phonon Thermal Conductivitymentioning
confidence: 99%
“…The efficiency of a thermoelectric (TE) device is governed by the device material's figure of merit, zT = σS 2 T /κ, where T , σ, S , and κ are the absolute temperature, the electrical conductivity, the Seebeck coefficient, and the total thermal conductivity (including the lattice component κ ph and the charge carrier component κ el ), respectively. Toward higher zT , defect engineering is invoked to (i) improve the power factor PF = σS 2 through tuning band structure, texture, and grain boundary; and (ii) suppress the κ ph through multiscale microstructures . While point defects are of vital importance, it is the synergy among various kinds of defects in defect engineering that underlies the high zT .…”
Section: Introductionmentioning
confidence: 99%
“…The inherent inter-dependence among α , ρ , and κ poses a major roadblock in realizing TE materials with higher ZT values 2 3 . In this context, tailoring the micro- and nano-structures at multiple length scales using advanced materials preparation methods has to a certain extent been able to decouple the inter-dependence among the TE properties; α , ρ , and κ 4 5 .…”
mentioning
confidence: 99%